Effects of copper sulfate, tri-basic copper chloride, and zinc oxide on weanling pig growth and plasma mineral concentrations - N W Shelton; Jim L Nelssen; G M Hill; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
Two 28-d experiments were conducted to determine the effects of increasing dietary zinc and copper levels on weanling pig performance. In each experiment, 180 weanling pigs (PIC, 21 d of age, 12.5 lb in Exp. 1 and 13.2 lb in Exp. 2) were allotted to 1 of 6 treatments with 5 and 6 replications in Exp. 1 and 2, respectively. Diets were fed in 2 phases (d 0 to 14 and 14 to 28), and the trace mineral premix provided 165 ppm zinc and 16.5 ppm copper to all diets. In Exp. 1, treatments were arranged as a 2 × 3 factorial with 2 levels of added copper from tri-basic copper chloride (TBCC; 0 or 150 ppm) and 3 levels of added zinc from zinc oxide (0, 1,500, or 3,000 ppm from d 0 to 14 and 0, 1,000, or 2,000 ppm from d 14 to 28). In addition, blood collected on d 14 was analyzed for plasma zinc, copper, and phosphorus concentrations. No copper × zinc interactions were observed (P>0.25) for any of the growth data. Addition of TBCC in-creased (P<0.03) ADG and ADFI over con-trol pigs from d 0 to 14, 14 to 28, and 0 to 28. Pigs fed increasing dietary zinc had increased (linear, P<0.003) ADFI during both phases and increased ADG from d 0 to 14 and 0 to 28. No effects were observed for blood metabolites in plasma copper; however, copper × zinc interactions were observed (P<0.03) for both plasma zinc and phosphorus. The interactions occurred because increasing dietary zinc oxide increased plasma zinc and phosphorus when TBCC was not included in the diet but had relatively little effect when TBCC was added to the diet. In Exp. 2, treatments were arranged as a 2 × 3 factorial with 2 levels of added zinc from zinc oxide (0 or 3,000 ppm from d 0 to 14 and 0 or 2,000 from d 14 to 28) and 3 copper treatments (control, 125 ppm copper from TBCC, or 125 ppm copper from copper sulfate). In addition, blood collected on d 14 and 28 was analyzed for plasma zinc, copper, and phosphorus concentrations. Again, no copper × zinc interactions (P>0.10) were observed for any performance data. Adding zinc oxide to the diet improved (P<0.03) ADG, ADFI, and F/G from d 0 to 14 and ADG and ADFI from d 0 to 28. Adding copper to the diet increased (P<0.05) ADG, ADFI, and F/G from d 0 to 14 and 0 to 28 with pigs fed copper sulfate having greater (P<0.02) ADG and ADFI from d 0 to 14 than pigs fed TBCC. Similar to Exp. 1, plasma zinc was increased (P<0.001) in pigs fed high levels of dietary zinc at d 14. Unlike many previous research trials, these two trials found additive effects to feeding high levels of dietary copper and zinc in diets for nursery pigs.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Copper; Weanling pigs; Zinc